2019
DOI: 10.1111/jcmm.14337
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal association between serum uric acid levels and multiterritorial atherosclerosis

Abstract: Multiterritorial atherosclerosis has dramatically increased annual risk of adverse cardiovascular events than atherosclerotic disease with single‐artery affected. Serum uric acid (SUA) is an important predictor of stroke and atherosclerosis; however, which is supported by few direct evidence based on cohort studies. A prospective cohort study including 2644 North Chinese adults aged ≥40 years was performed in 2010‐2012 to investigate the association between SUA and multiterritorial vascular stenosis. Hyperuric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 42 publications
(101 reference statements)
1
28
0
Order By: Relevance
“…In a large cross-sectional study, Shankar et al reported that higher serum UA levels were associated with peripheral arterial disease (defined as ABI < 0.9) in the US general population [ 49 ]. In addition, Song et al reported that serum UA levels were associated with asymptomatic polyvascular stenosis, including peripheral arterial disease, in a prospective cohort study of 2644 adults [ 50 ]. Possible reasons for the difference between the results of the present study and previous studies are as follows.…”
Section: Discussionmentioning
confidence: 99%
“…In a large cross-sectional study, Shankar et al reported that higher serum UA levels were associated with peripheral arterial disease (defined as ABI < 0.9) in the US general population [ 49 ]. In addition, Song et al reported that serum UA levels were associated with asymptomatic polyvascular stenosis, including peripheral arterial disease, in a prospective cohort study of 2644 adults [ 50 ]. Possible reasons for the difference between the results of the present study and previous studies are as follows.…”
Section: Discussionmentioning
confidence: 99%
“…When the SUA level was above 5.2 mg/dl, arterial stiffness was increased in healthy Korean men 34 . Some longitudinal studies have shown that uric acid was a risk factor for arteriosclerosis, the relationship was www.nature.com/scientificreports www.nature.com/scientificreports/ more pronounced in men 35 . Shin's 21 and Tomiyama's 36 studies showed an insignificant relationship between uric acid and arterial stiffness in women with normal uric acid level.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, studies have shown that with the increase of age, male individuals with higher SUA values had an accelerated increase in PWV, which was not related to major 37 . A prospective cohort study of adults in northern China aged 40 years and older showed that uric acid was associated with arteriosclerosis, but not in women 35 . Previous studies have shown that SUA was an independent risk factor for arteriosclerosis in women older than 55 years 1 , but our studies showed that there were not statistically significant in females.…”
Section: Discussionmentioning
confidence: 99%
“…In a prospective cohort study by Song M et al . [19] in north Chinese adult UA was found to be an independent risk factor for incidence of extracranial carotid atherosclerosis in both genders. Also José Carlos Arévalo-Lorido et al .…”
Section: Discussionmentioning
confidence: 99%